Sustainability evaluation of Concentrated Solar Power (CSP) projects under Clean Development Mechanism (CDM) by using Multi Criteria Decision Method (MCDM). (October 2018) - Simsek, Yeliz; Watts, David; Escobar, Rodrigo
Abstract: Climate change has caused growing concern in the international community. The Kyoto Protocol was signed by a majority of the world with the clear intention of reducing emissions. Clean Development Mechanism (CDM) is a part of the Kyoto Protocol and allows industrialized countries to reduce their emission by making contribution to developing countries. In this study, several research papers related to sustainability and multi-criteria analysis of energy projects were reviewed and classified based on their focus, motivation and contribution to achieve a comprehensive summary. Additionally, this paper presents a review of multi criteria decision methods and sustainability indicators under five pillars: technical, economic, social, environmental, and risk. Moreover, sustainability analysis of worldwide CDM concentrated solar power (CSP) projects was performed by using MAUT method. The analysis was repeated based on several scenarios including different criteria and criteria weights. The purpose of this research is proposing a framework and providing an understanding for decision makers to evaluate the sustainability of CDM energy projects. This work can provide perceptions to future installations and further insights for the development of sustainable CDM energy projects around the world.